WO3@MOF heterostructure in-situ transformed and deposited on La-Bi2WO6-BiFeWOx composite with enhanced photocatalytic performance for degradation of harmful and toxic substances produced by tobacco - Li, Jingxin; Jing, Yanqiu; Zhang, Shuo; Rao, Chaoqi; Luo, Dongsheng; Xi, Feihu; Wu, Jinming; He, Aimin; Shen, Wei; Zhang, Liang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•La-Bi2WO6-BiFeWOx-WO3@MOF was successfully synthesized using hydrothermal and in-situ transformation methods.•La-Bi2WO6-BiFeWOx-WO3@MOF efficiently degrades phenol (98.62%), nicotine (92.41%), benzopyrene (81.74%), and nitrosamine (98.23%).•La-Bi2WO6-BiFeWOx-WO3@MOF demonstrates efficient separation and transfer of photo-generated electron-hole pairs.•The primary active radicals generated by La-Bi2WO6-BiFeWOx-WO3@MOF are ·OH and ·O2–. Nowadays, tobacco is widely cultivated, and there are millions of people who smoke around the world. The cultivation of tobacco, along with the handling of cigarettes and the consumption of tobacco products, can produce numerous harmful and toxic substances. Many researchers are working diligently to eliminate these harmful and toxic substances. However, the results have been minimal. In this paper, we successfully prepared a novel La-Bi2WO6-BiFeWOx-WO3@MOF using hydrothermal and in-situ transformation methods. All samples were thoroughly investigated using various characterization techniques, including XRD, SEM, TEM, XPS, UV–Vis absorption spectra, transient photocurrent responses, and electron spin resonance. Furthermore, La-Bi2WO6-BiFeWOx-WO3@MOF was utilized as a catalyst for the degradation of harmful and toxic substances produced by tobacco, including phenol, nicotine, benzopyrene, and nitrosamines. The results indicate that La-Bi2WO6-BiFeWOx-WO3@MOF exhibits efficient separation and transfer of photo-generated electron-hole pairs under visible light irradiation. La-Bi2WO6-BiFeWOx-WO3@MOF also exhibits excellent photocatalytic activity, efficiently degrading phenol (98.62%), nicotine (92.41%), benzopyrene (81.74%), and nitrosamine (98.23%). Furthermore, the effects of varying catalyst dosage, phenol concentration, and pH values, as well as the degradation of nicotine, benzopyrene, and nitrosamine by La-Bi2WO6-BiFeWOx-WO3@MOF, were also investigated. The main active radicals are ·OH and ·O2– during the degradation process. Finally, a potential degradation mechanism for phenol, nicotine, benzopyrene, and nitrosamine by La-Bi2WO6-BiFeWOx-WO3@MOF is proposed.